(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study was conducted in order to secure the validity of the license system development for education training experts with the multidisciplinary knowledge of dying well by identifying the need for the dying well education and license system. Method/Statistical Analysis: A total of 128 adults aged 19 or older who visited D Station in D city from April 14 to May 14, 2018 was randomly selected and surveyed, and the statistical program R was used for the analysis. Findings: All subjects answered that dying well education is necessary, and that educators suitable for dying well education included experts, medical professionals, and religious leaders who received dying well education. Of the educational contents, care for terminal patients (hospice) and psychological healing were the most needed. There was a correlation between experts who received dying well education, terminally ill patients and their families, and nursing and elderly hospital workers. Improvements/Applications: In order to secure the expertise of dying well education in the future, it is necessary to form a curriculum based on the results of this study and to train death education experts with multidisciplinary knowledge through the verification of a professional national license.